Opportunities for Intercultural Environment Creation in Ukrainian Agrarian University - Marina Bilotserkovets; Tetiana Fomenko; Yuliia Lushchyk (Educational Challenges)
This study aims to highlight the significance of creating intercultural competence among students in Ukrainian higher education institutions (HEIs), especially in the context of European integration. The goal is to investigate the potential impact of Euro Union (EU) educational policies and the Association Agreement between Ukraine and the EU on students’ intercultural competence, and to offer recommendations for the effective implementation of intercultural education.